2019
DOI: 10.1038/s41431-019-0390-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of telephone genetic counselling to facilitate germline BRCA1/2 testing in women with high-grade serous ovarian cancer

Abstract: Systemic healthcare issues and geographical challenges restrict women's access to BRCA1/2 testing to inform the use of tailored treatments for high-grade serous ovarian cancer. Consequently, BRCA1/2 testing in this population is low and improved testing pathways are urgently needed. This study aimed to determine the acceptability and feasibility of telephone genetic counselling (TGC) to facilitate treatment-focused BRCA1/2 testing in Australia for women with high-grade serous ovarian cancer. Women who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…This model of clinical BRCA1/2 JFM screening is aligned with the shift away from the traditional in-person counselling model and towards telehealth genetic services (Zierhut et al 2018) to increase accessibility of genetic counselling and testing (Rayes et al 2019). In a recent study evaluating telephone genetic counselling services in women affected with highgrade serous ovarian cancer, both BRCA1/2 carriers and noncarriers reported accepting, satisfactory attitudes and minimal regret towards testing (Tutty et al 2019), which are largely consistent with the positive responses of our cohort. It was also noted that carriers were not observed to carry additional psychosocial burden as compared to noncarriers.…”
Section: Discussionsupporting
confidence: 83%
“…This model of clinical BRCA1/2 JFM screening is aligned with the shift away from the traditional in-person counselling model and towards telehealth genetic services (Zierhut et al 2018) to increase accessibility of genetic counselling and testing (Rayes et al 2019). In a recent study evaluating telephone genetic counselling services in women affected with highgrade serous ovarian cancer, both BRCA1/2 carriers and noncarriers reported accepting, satisfactory attitudes and minimal regret towards testing (Tutty et al 2019), which are largely consistent with the positive responses of our cohort. It was also noted that carriers were not observed to carry additional psychosocial burden as compared to noncarriers.…”
Section: Discussionsupporting
confidence: 83%
“…of included studies (44%) were from North America [34-39, 41, 44-47, 54] (Table 2). The 25 studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][51][52][53][54][55] (93%) described interventions to increase access to GC and GT through mainstreaming or UTS initiatives (S4 Table ). The study designs found were retrospective or prospective cohort studies with concurrent or historical controls (44%) [34, 36, 37, 42-47, 54, 55] or case series that reported on intervention outcomes (56%) [29-33, 35, 38-41, 48, 51-53] (Table 2).…”
Section: Plos Onementioning
confidence: 99%
“…Quality assessment. Fifty-six percent of the studies (n = 14) received a poor AHRQ rating due to the study design-case series with no comparator [29-33, 35, 38-41, 48, 51-53], selection bias in the use of a single site health system [29,30,39,40,47,48] and/or no statistical adjustment for patient population differences or assessment of confounders [30,42,47] (S5 and S6 Tables). Thirty-six percent of the studies received a fair to good AHRQ rating (n = 9) and were cohort studies with a historical or concurrent comparator [34, 36, 37, 44-47, 54, 55].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, mainstreaming genetic testing has been evaluated as part of the medical oncology visits, [1][2][3] while the feasibility of nonin-person visits has been tested to ease and expand access to cancer genetic counseling services. [4][5][6][7][8] Since the COVID-19 outbreak, telephone contact with patients has been universally used by health-care professionals to maintain a partial continuity with them. Scientific oncology societies have recommended avoiding in-person visits during the lockdown and encourage the use of telemedicine especially for stable patients and those with oral therapies.…”
Section: Introductionmentioning
confidence: 99%